Differential regulation of NPY and SP receptor expression in STRO‐1+ve PDLSCs by inflammatory cytokines. (13th November 2021) - Winning, Lewis; El Karim, Ikhlas A.; Linden, Gerard J.; Irwin, Christopher R.; Killough, Simon A.; Lundy, Fionnuala T.
Abstract: Objectives: The aims of this study were to investigate neuropeptide receptor expression regulation on STRO‐1 +ve periodontal ligament stem cells (PDLSCs) in response to inflammatory cytokines and to investigate a potential osteogenic effect of neuropeptides. Background: Nerve fibres innervating the periodontal tissues in humans contain several neuropeptides including neuropeptide Y and substance P. The role of neuropeptide receptors on PDLSCs, including their response to the local inflammatory environment of periodontitis, is currently unknown. Methods: A homogenous population of STRO‐1 +ve PDLSCs was prepared by immunomagnetic separation of cells obtained by the tissue out‐growth method from healthy premolar teeth from a single donor. Regulation of gene expression of the neuropeptide Y Y1 receptor and substance P receptor tachykinin receptor 1 was investigated. A potential osteogenic effect of neuropeptide Y and substance P was also investigated by measuring alkaline phosphatase (ALP) activity, Alizarin red staining and quantifying osteogenic gene expression. Results: Treatment of STRO‐1 +ve PDLSCs with tumour necrosis factor‐alpha or interleukin 1‐beta up‐regulated the expression of the neuropeptide Y's Y1 receptor, but down‐regulated substance P's receptor. Significantly increased ALP activity was observed in STRO‐1 +ve PDLSCs treated with neuropeptide Y but not substance P. Further studies showed that neuropeptide Y had a modest osteogenic effect on cells at both a functional level and a gene level. Conclusions: Expression of the neuropeptide Y Y1 receptor gene on STRO‐1 +ve PDLSCs was sensitive to local inflammatory cytokines. Treatment of cells with neuropeptide Y was found to produce a modest enhanced osteogenic effect.